Legitimizing the past. Autonomous tendencies and representations of Santa Fe identity in the autobiographical narrative of governor Domingo Crespo (c. 1847–1854) (Quinto Sol, 2025)
During the central decades of the 19th century, and before Argentine historiography acquired more scholarly or scientific features, it was the autobiographical genre that offered the first representations of the post-revolutionary past in ​​the Río de la Plata and the Paraná coast area. From a testimonial, individual and subjective perspective, the memories served to provide an initial reconstruction of the events and collaborated in the construction of identities, both at the national and regional, provincial and local level. This function was fulfilled by the Memoirs of Don Domingo Crespo (c. 1847-1854). Crespo was a resident and leading man of Santa Fe who, among other relevant positions, served as governor -due to his Lopista and anti-Rosista political career that brought him closer to Justo José de Urquiza- at the time of the Argentine constitutional organization. His Memoirs are analyzed in this article as an example of autobiographical writing, based on new approaches that postulate the usefulness of this type of texts for studies of the history of historiography, and as a story that is a justification of the autonomous and federal tendencies supported by the province of Santa Fe and by Estanislao López and his men, against Buenos Aires centralism.
Keywords: historiography; historians; federalism; memoirs